Ways of HIV transmission in China: The effect of age, period, and cohort - Wang, Tang; Gu, Yaohua; Ran, Li; Tan, Xiaodong; Peng, Shuzhen (Frontiers in Public Health, 2022)
Background AIDS is a global pandemic caused by HIV, which is transmitted through human behavior including sexual intercourse, intravenous drug injection, blood transfusion. Rare studies focused on evaluating the effect of culture, society, and HIV-related policy in adjusting people’s HIV-related behavior, i.e., ways of HIV transmission. Methods Focusing on the new HIV infections each year in Hubei, China during 1995-2020, our study used Hierarchical Age-Period-Cohort model to analyze the effects of age, period, and cohort on the trends of ways of HIV transmission. Results A total of 34636 HIV infection was reported during 1995 to 2020. The number of new HIV infections in Hubei presented a general upward trend. For HIV infection during 1995 and 2020, age (-0.099, P<0.001), squared age (-0.002, P<0.001) had negative effect on the rate of blood transmission. For HIV infection via sexual transmission, age (0.143, P<0.001), squared age (0.002, P<0.001) had positive effects on the rate of sexual transmission. Significant period and cohort effects on ways of HIV transmission among Chinese population were also observed. Conclusion Sexual and blood transmission are the two main ways of HIV infection in China and Hubei. The trend of blood transmission is in accordance with the wave of blood merchants in the early 1990s in China. The trend of sexual transmission indicate the increasing need to address safety sexual behavior among older population and later generation. More tailored, innovative and diverse HIV prevention strategies are needed to reach and work on population with high risky behavior.